PERSEPSI GURU PENDIDIKAN JASMANI SEKOLAH MENENGAH ATAS NEGERI SE-KOTA YOGYAKARTA TENTANG PENILAIAN DOMAIN AFEKTIF - Faradika Ratria Prastawa dan Sismadiyanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
This study discusses the physical education teachers’ perceptions of State High School as the city of Yogyakartaon the affective domain assessment . The objectives are to determine the amount of physical education teachers’perceptions of State High School as the city of Yogyakarta on the affective domain assessment in general, as wellas indicators of attitudes, interests, self-concept, value s, and morals. This research is a descriptive study with onevariable, namely: physical education teachers’ perceptions of the affective domain assessment. The population is theentire physical education teacher High School as the city of Yogyakarta, which amounted to 22 people. Instrumentused to collect data using questionnaires. To analyze the data collected, researchers using quantitative descriptiveanalysis techniques with percentages. The results showed that physical education teacher’s perceptions of StateHigh School as the city of Yogyakarta on the affective domain assessment in the category with a percentage of36.36 %. In the affective domain indicator, attitude indicator in the high category with the percentage of 54.55 %,an indicator of interest in the category with a percentage of 36.36, an indicator of self-concept in the category withthe percentage of 54.55 %, the indicator value in the high category with a percentage of 50 %, indicators of moralein the category with the percentage of 27.27 % while the biggest indicator in the affective domain is the attitudeindicator with a percentage of 86.52 % approval. From the analysis of the 5 indicators, trend of State High Schoolphysical education teacher as the city of Yogyakarta in the affective domain valuation assessment focuses on theattitude indicator and indicators of interest.